The Effects of HFOV-VG vs HFOV on Bronchopulmonary Dysplasia and Neurobehavioral Development in Preterm Infants with Perinatal Acute Respiratory Distress Syndrome - Tao M; Yan L; Hu Y; Shen L; Cai N (International Journal of General Medicine)
Min Tao,* Ling Yan,* Yuan Hu, Leilei Shen, Na Cai Department of Pediatrics, The First Hospital Affiliated to Army Medical University, Chongqing, 400038, People’s Republic of China*These authors contributed equally to this workCorrespondence: Na Cai, Department of Pediatrics, The First Hospital Affiliated to Army Medical University, No. 30, Gaotanyan Street, Chongqing, 400038, People’s Republic of China, Tel +86-23-68766213, Email caina@tmmu.edu.cnObjective: This study aimed to explore whether high-frequency oscillatory ventilation with volume-guarantee (HFOV-VG) strategy could reduce the incidence of bronchopulmonary dysplasia (BPD) and improve poor neurological prognosis in premature infants with perinatal acute respiratory distress syndrome (NARDS) compared with high-frequency oscillatory ventilation (HFOV) alone.Methods: This retrospective single-center study conducted in the neonatal intensive care unit (NICU) from January 2016 and December 2023. One hundred and seventy-two premature infants (32 weeks ≤ gestational age < 37 weeks) with NARDS were enrolled. Infants were categorized into two groups based on ventilation strategy: HFOV-VG (n = 70) and HFOV (n = 102). The demographic data, perinatal factors, primary and secondary outcomes were compared. Univariate and multivariate logistic regression analyses were performed to assess the association between the ventilation strategy and primary outcomes.Results: The invasive mechanical ventilation duration and incidence of BPD in HFOV-VG group were lower than those in HFOV group. There were no significant differences in complication, and the scores of neurobehavioral development between the two groups of children who were followed up until correct age of 6 months. The multivariate logistic regression analysis identified that the ventilation strategy of HFOV-VG was an independent protective factor of BPD. However, HFOV-VG was not associated with a statistically significant improvement in short-term neurodevelopmental outcomes. Subgroup analysis showed that there were no significant interactions in any of the subgroups except for birth weight subgroup. The association between HFOV-VG mode and the incidence of BPD was more pronounced in neonates with birth weight < 2500g.Conclusion: The ventilation strategy of HFOV-VG was a promising lung protective mode for premature infants with perinatal ARDS, which can shorten mechanical ventilation duration and may reduce the incidence of BPD. However, it did not seem to be superior to HFOV in improving short-term neurodevelopmental outcomes.Keywords: acute respiratory distress syndrome, bronchopulmonary dysplasia, high frequency oscillatory ventilation, high-frequency oscillatory ventilation with volume-guarantee, neurobehavioral development